Induction of zinc conjugated with Doxorubicin for the prevention of aggregating β-catenin in the Wnt signaling pathway investigated through computational approaches - Gomathi Rajagopal; Balajee Ramachandran; Paradesi Deivanayagam; Venkatesan Srinivasadesikan; Boomi Pandi; Saravanan Muthupandian; Rajamanikandan Sundarraj; Goyitom Gebremedhn Gebru (PLoS ONE, 2025)
Canonical Wnt signaling plays a key role in tumor cell proliferation which correlates with the accumulation of β-catenin resulting inactivation of the network of targets such as GSK3β, Axin, CK1. Uncontrolled expression of β-catenin leads to different types of cancers and other diseases such as sarcoma and mesenchymal tumor formation. However, β-catenin is an attractive target for cervical cancer. In the present study, the compounds such as Doxorubicin and Zinc conjugated with Doxorubicin were screened against β-catenin using Molecular Docking, Molecular Dynamics Simulation, MM/GBSA, and DFT approaches to explore their insights. The study further demonstrated that the binding energy of Zn conjugated with Doxorubicin has shown -7.2 kcal/mol and Doxorubicin registers -5.9 kcal/mol against β-catenin. The disruption between the β-catenin/Tcf-4 complex was observed through the Zinc-Doxorubicin complex, both the proteins are separated about 12 Å. The Zn-Doxorubicin was stabilized with the hydrophobic residues such as Val349 of β-catenin and Phe21 of Tcf-4. The DFT analysis using the B3LYP/6-31g(d,p) method explores that Zn-doxorubicin in complex with the binding site residues has shown the HOMO-LUMO gap of 2.55 eV. The binding free energy calculations exhibit the Zn conjugated Doxorubicin favors in the study by showing ~ 3 kcal/mol difference with Doxorubicin. The Zn-conjugated Doxorubicin will be discussed in the context of cervical cancer with the hope of improving drug efficacy and reducing toxicities for the betterment of the patient’s quality of life.